Needs of cancer patients during the period of treatment of late complications of cancer - Mikalajūnaitė, Germantė; Martikaitytė, Justina; Gierasimovič, Zita (Slauga. Mokslas ir praktika, 2023)
Cancer is the most common cause of death worldwide. Nursing services provided in the late stage of cancer complications improve the quality of life of patients, accelerate the recovery process or help them find inner spiritual peace. The ability of nurses to express empathy and apply motivational interviews has an impact on patients becoming stronger psychologically and physically. The psychological need is effective when a teamwork model is used. The aim of the research – to analyze scientific literature on the needs of patients in the stage of late complications of cancer treatment. Methods of research. Systematic research of the scientific literature was conducted using PubMed, BMJ, Elsevier, The Lancet oncology, IMJ, Google Scholar, World Health Organisation electronic databases. The results showed that the side effects of treatment can last for years in cancer patients in the late stage of complications. The nursing needs are directed to the continuous care of oncological patients, assessment of health status. Teamwork helps to involve the patient in the services provided, to motivate the patient’s actions, feedback is important too. Educational activities of the nursing staff are aimed at promoting a healthy lifestyle, planning daily activities that help reduce fatigue, pain, and maintain muscle mass.